Screening and confirmatory analysis of recombinant human erythropoietin for racing camels' doping control. Issue 6 (10th March 2020) - Delcourt, Vivian; Garcia, Patrice; Chabot, Benjamin; Loup, Benoit; Remy, Pierre; Popot, Marie‐Agnès; Bailly‐Chouriberry, Ludovic
Abstract: Recombinant human erythropoietin (rHuEPO) belongs to the therapeutic class of erythropoiesis stimulating agents (ESAs) due to its implication in the creation pathway of red blood cells and thus enhancement of oxygenation. Because of this bioactivity, rHuEPO has been considered as a major doping agent in sports competitions for decades. Over the years, doping control laboratories designed several analytical strategies applied to human and animal samples to highlight any misuse. Even though multiple analytical approaches have been reported, none has yet been dedicated to racing camels. Here, we describe an analytical strategy to test camel plasma samples at screening using an ELISA assay and a targeted nano‐liquid chromatography–high‐resolution tandem mass spectrometry for confirmatory analysis. The method was validated and has been successfully applied to post‐race samples, allowing the detection of a positive case of rHuEPO administration. Abstract : Validation of ELISA screening and nanoLC–HRMS confirmatory analyses for rHuEPO in camel plasma samples through in‐depth sequence analysis and novel target peptide definition.